2018
DOI: 10.1021/acsami.8b04982
|View full text |Cite
|
Sign up to set email alerts
|

Pd@HyWO3–x Nanowires Efficiently Catalyze the CO2 Heterogeneous Reduction Reaction with a Pronounced Light Effect

Abstract: The design of photocatalysts able to reduce CO to value-added chemicals and fuels could enable a closed carbon circular economy. A common theme running through the design of photocatalysts for CO reduction is the utilization of semiconductor materials with high-energy conduction bands able to generate highly reducing electrons. Far less explored in this respect are low-energy conduction band materials such as WO. Specifically, we focus attention on the use of Pd nanocrystal decorated WO nanowires as a heretofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 41 publications
2
52
0
Order By: Relevance
“…Furthermore, the CB positions of the two samples were higher than that of the CO 2 /CH 3 OH redox potential but lower than that of the CO 2 /CO redox potential, indicating that under suitable light irradiation, these two samples can reduce CO 2 into CH 3 OH, but not into CO, at least in theory. However, under some special circumstances, such as the presence of reduced W 5+ and other defects in the particle surface, CO 2 can be reduced to CO below the potential of −0.53 V as the activation energy of CO 2 reduction to CO decreases in the presence of specific ions and defects [23,24,26,31]. In this study, the samples' photocatalytic activities were evaluated through CO 2 reduction under the full spectrum of 300 W Xe lamp.…”
Section: Crystalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the CB positions of the two samples were higher than that of the CO 2 /CH 3 OH redox potential but lower than that of the CO 2 /CO redox potential, indicating that under suitable light irradiation, these two samples can reduce CO 2 into CH 3 OH, but not into CO, at least in theory. However, under some special circumstances, such as the presence of reduced W 5+ and other defects in the particle surface, CO 2 can be reduced to CO below the potential of −0.53 V as the activation energy of CO 2 reduction to CO decreases in the presence of specific ions and defects [23,24,26,31]. In this study, the samples' photocatalytic activities were evaluated through CO 2 reduction under the full spectrum of 300 W Xe lamp.…”
Section: Crystalsmentioning
confidence: 99%
“…Furthermore, researchers have found that the introduction of oxygen vacancies and reduced W 5+ in WO 3 can also significantly improve its photocatalytic CO 2 reduction activity. The creation of oxygen vacancies and W 5+ in WO 3 increases the surface negative charge density and the number of active sites, which in turn increases CO 2 adsorption and activation [18,25,26]. For example, Xi et al [27] prepared ultrathin W 18 O 49 nanowires to investigate their photocatalytic CO 2 reduction property.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Pd/H y WO 3− x , formate intermediates were not observed in the in situ DRIFTS measurements. This suggests Ba II surface sites facilitate the adsorption/accumulation of CO 2(g) as carbonates and bicarbonates to the extent that the subsequent hydrogenation steps are slower and become rate limiting (Scheme ).…”
Section: Methodsmentioning
confidence: 70%
“…Notwithstanding the challenges of establishing a unified national or international renewable energy policy, myriad science and engineering projects are under development around the world to accelerate and enable the transition from a non-renewable energy supply to a renewable one. These research projects and industry initiatives focus on many aspects of this endeavour such as new materials and technologies for renewable energy harvesting 10–15 , new topologies and methods for stabilizing power grids 12,16–18 , energy storage 16,19,20 , efficient usage of energy 12,21,22 and renewable power-based transportation fuels and industrial chemicals mostly from captured carbon dioxide or industrial waste gas streams 14,15,23–27 . The latter involves hydrogen as a potential future fuel but also as an important intermediate for the production of synthetic hydrocarbons.…”
Section: Need For Changementioning
confidence: 99%
“…Moreover, in the future direct conversion of solar radiation, CO 2 and water into hydrocarbon fuels may reach a competitive status compared to the indirect way of first generating power from photovoltaics or concentrated solar energy and then splitting water or CO 2 by electrolysis. Focused research on photocatalytic solar fuels is underway worldwide, for example at the Joint Center for Artificial Photosynthesis (JCAP) of the California Institute of Technology in Pasadena, CA, USA 11,30,31 , the Helmholtz Center Berlin, Germany, and the University of Toronto, Canada 10,14 , to name only a few of the many institutions active in this field. Technology for direct solar thermal fuels is being developed at the Swiss Federal Institute of Technology (ETH) in Zürich, Switzerland, the German Aerospace Center (DLR) in Cologne, Germany, and the Weizman Institute of Science in Rechovot, Israel (see e.g.…”
Section: The Vision Of “Crowd Oil”mentioning
confidence: 99%